Perovskanol, a new sesquiterpenoid with an unprecedented skeleton from Perovskia Abrotanoides. Issue 15 (3rd August 2021) - Karimzadeh, Seyedeh Masoomeh; Moridi Farimani, Mahdi; Amiri, Mohammad Sadegh; Tabefam, Marzieh; Alilou, Mostafa; Stuppner, Hermann
Abstract: Phytochemical investigation of the aerial parts of Perovskia abrotanoides (Lamiaceae) by normal phase column chromatography resulted in the isolation of perovskanol (1 ), a novel sesquiterpenoid possessing a 5/7/5 fused carbon ring skeleton. The structure of 1 was established by comprehensive spectroscopic data analysis including 1 D and 2 D NMR and HRESIMS. The antiprotozoal activity of compound 1 was evaluated against Trypanosoma brucei rhodesiense, T. cruzi, Leishmania donovani, Plasmodium falciparum and no promising activities were shown against all parasite tested. Graphical Abstract: